Peningkatan Keahlian Identifikasi Peluang Usaha Bagi Calon Wirausaha di Kota Kendari - Ernawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Covid-19 pandemic which has an impact on the economic slowdown encourages the importance of skill in identifying business opportunities for entrepreneurs. The community service program aims to increase the skills of potential entrepreneurs in Kendari City in identifying business opportunities during the Covid-19 pandemic. The activity was carried out through online learning for one month, starting from 12 June to 13 July 2020 with 30 participants (potential entrepreneurs). The stages of online learning were done in 3 sessions. The results of the program showed that participants experienced an increase in understanding and interest from before and after the implementation of the program for all indicators, namely: confidence in the ability to become an entrepreneur, views on the entrepreneurial profession, interest in becoming entrepreneurs, views on risks and opportunities during the pandemic. Participants assume that if they have a business during a pandemic, they will be able to survive. Participants also believe that business is not dependent on capital. Participants believe that they will be very capable of dealing with the business obstacles. Online learning activities that are carried out are very effective, which is shown by the perception of potential entrepreneurs who are able to identify opportunities during the pandemic, as well as the objectives of the community service program.